A Literature Survey on Password Extraction via Reconstructed Wireless Mouse Trajectory (International Journal of Engineering and Computer Science, 2017)
Since the mouse movement data are not encrypted secret information such as password can be leaked through the displacement of mouse.Two attacks are proposed here, the prediction attack and replay attack, which can rebuild the onscreen cursor trajectories by sniffing mouse movement data. Two inference strategies are used to discover pass-words from cursor trajectories.This work is the survey to demonstrate the different techniques and tools in privacy leakage from raw mouse data.